Direct-Acting Antiviral Use for Genotype 1b Hepatitis C Patients with Associated Hematological Disorders from Romania - Iosif Marincu; Felix Bratosin; Manuela Curescu; Oana Suciu; Mirela Turaiche; Bianca Cerbu; Iulia Vidican (Medicina, 2021)
Background and objectives: this study assessed variations in the blood parameters of patients with hematological disorders infected with HCV throughout a 12-week interferon-free treatment regimen. Materials and methods: We followed a total of 344 patients suffering from chronic hepatitis C, infected with the 1b genotype and concomitant hematological disorders, who benefited from the direct-acting antiviral (DAA) therapy in our clinic. Seven of the most routinely checked blood parameters were analyzed, namely, hemoglobin, leucocyte count, neutrophils, erythrocyte count, platelet count, ALT, and total bilirubin level. In total, 129 patients received a treatment scheme comprising ombitasvir, paritaprevir, ritonavir, and dasabuvir, while the 215 other patients received a sofosbuvir and ledipasvir regimen. Results: Patients enrolled in the study showed remarkably increased ALT levels in the first four weeks of DAA treatment, normalizing to levels below 40 U/L by the end of regimen. There were no other blood parameters that worsened throughout the 12-week regimen to levels below our laboratory’s normal range. After 12 weeks of DAA therapy, 309 patients (90%) achieved SVR. Conclusions: Our findings are consistent in evaluating the efficacy and tolerability of direct-acting antivirals for 1b genotype HCV infected patients with associated hematological malignancies under remission, and other hematological disturbances, that were previously unsuccessfully treated with a pegylated interferon regimen. Thus, paving a pathway for government-funded programs being implemented in this direction.